Formant characteristics of Malay vowels - Izzad Ramli; Nursuriati Jamil; Norizah Ardi (Institute of Advanced Engineering and Science, 2020)
The purpose of this study was to investigate and examined the eight vowels formant characteristic of Malay language. Previous research of Malay language only investigated six basic vowels /a/, /e/, /i/, /o/, /u/, /ə/. The vowels /ɔ/, /ε/ that usually exist in a dialect were not included in the previous investigations. In this study, the vowels sound were collected from five men and four women producing the vowels /a/, /e/, /i/, /o/, /u/, /ə/, /ɔ/, /ε/ from different regions and dialects in Malaysia. Formant contours, F1 until F4 of the vowels were measured using interactive editing tool called Praat. Analysis of the formant data showed numerous differences between vowels in terms of average frequencies of F1 and F2, and the degree of overlap among adjacent vowels. When compared with the International Phonetic Alphabet (IPA), most pronunciation of the Malay vowels were at the same position but the vowel /ε/ seen more likely to become a front vowel instead of a central vowel. Consequently, vowel features of the two Malay allophones /ɔ/ and /ε/ were documented and added to the IPA vowel chart. The findings form the fundamental basis for further research of speech synthesis, speech rehabilitation and speech reproduction of the Malay language.